Modelos Asociativos: Una necesidad del sector madera y muebles de la ciudad de Barranquilla para mejorar su productividad y competitividad (2013)
The following article is based on the results of the research project: “Design of a cooperative relationship model SENA - Industrial sector - Government - University”. Basically looking for the relevance between the needings for the wood and furniture sector in the city of Barranquilla, its alliances with universities and the goverment to obtain a better and more productive, to be more competitive in regional, national and international markets. To achieve this, some tools must be used to reach that goal, specifically, associative models, which could support improvement programs in connection with the ultimate objective to increase productivity and competitiveness of Mipymes (micro, small and medium enterprises) belonging to that sector and are domiciled in the city of Barranquilla and its metropolitan area. Its development consists of an introduction in which is expressed where the study was conducted, which models were applied and how many Mipymes participated in the sample. Subsequently, an analysis of the obtained results from surveys applied to the SENA as training center that could help support these programs due to its resources, and the application of another survey to 17 Mipymes of the sector, where the following six levels were identified: business management, human talent, training, infrastructure, continuous improvement and shopping links. Finally, could be concluded that the results of field work suggests the implementation of associative models applied in the Mipymes sector of wood and furniture in the metropolitan area of Barranquilla, as a necessary tool to improve and increase their productivity and competitiveness compared with other companies in the region.